A novel approach on the study of cure kinetics for rheological isothermal and non-isothermal methods. (1st April 2019) - Zhongliang, Ma; Le, Qi; Wei, He; Liming, He
Abstract: The cure kinetics of GAP (glycidyl azide polymer) special propellant have been studied by rheological isothermal and non-isothermal methods. Arrhenius equation has been proposed to describe the dependence of storage modulus on the temperature. Thus, one can distinguish cure effect from temperature effect resulting in storage modulus change. The conversion a has been calculated by a novel method, according to which rheological non-isothermal test can be applied and the isothermal test can be optimized. Apparent activation energy has similar trends and similar values of parameters has been concluded for isothermal and non-isothermal tests. New kinetic equations had been established and showed great agreement with experimental data both in isothermal and non-isothermal tests. Altogether, the temperature effect should be distinguished while calculating the conversion degree a . Rheological isothermal and non-isothermal method should be used to investigate the mechanism and kinetics of thermosetting reactions, especially for heterogrnerous reactions. The obtained knowledge of the curing kinetics will form a contribution to the study of heterogrnerous reactions.